Macroeconomic impact of Covid-19 in developing Asia - Yasuyuki Sawada; Lea R. Sumulong (Asian Development Bank Institute (ADBI), 2021)
This paper summarizes unprecedented adverse health and economic impacts as well as policy responses in the Asia and Pacific region and the rest of the world generated by the coronavirus disease (COVID-19) pandemic in 2020. By the end of 2020, over 80 million people had been infected, with developing Asia accounting for 17% of cases. As the pandemic progressed, the Asian Development Bank (ADB) carried out assessments of the impacts on the global economy as well as on the overall economies of its developing members, updating the analyses as more information became available. On the whole, five economic impact assessments were undertaken in 2020 - one each in March, April, May, June, and December. Based on the latest analysis, relative to a no-COVID-19 baseline, global losses were estimated at 5.5%-8.7% of world GDP in 2020 and 3.6%-6.3% of world GDP in 2021, with the corresponding losses for developing Asia amounting to 6.0%-9.5% of regional GDP and 3.6%-6.3% of regional GDP in 2020 and 2021, respectively. These impacts largely originate from declines in domestic demand and tourism, and from global spillovers. As a result of these losses, real GDP of the developing Asian region is estimated to have contracted by 0.4% in 2020. A partial recovery is expected in 2021, with regional growth projected at 6.8%. Further analyses were carried out to study the impacts on: micro, small, and medium-sized enterprises; employment; migration and remittances; poverty; nonperforming loans; and debt sustainability. Faced with wide-ranging unfavorable impacts, governments and multilateral lenders responded aggressively to mitigate the adverse effects of the pandemic. Many governments provided direct income support to households and businesses to help them cope with the economic shock. Meanwhile, multilateral lenders like ADB readily provided support in terms of finance, knowledge, and partnerships. In addition, ADB launched a 9 billion vaccine facility, the Asia Pacific Vaccine Access Facility, in December 2020, to support its low- and middle-income member countries in the effective procurement and delivery of COVID-19 vaccines. Despite the availability of vaccines, however, there is no room for complacency, as it will take years for the global population to achieve herd immunity, especially amidst the emergence of new, more transmissible, virus strains. While COVID-19 has brought about long-lasting changes to the global economy, it is up to policymakers to use this opportunity to adapt COVID-19 responses to address longer-term challenges.
Keywords: E17; H3; H6; I15; I32; 330; COVID-19; economic impact; policy response